The rise and fall of ancient Egypt - Wilkinson, Toby A. H. (New York : Random House, 2010)
In this magnificent history, Toby Wilkinson combines grand narrative sweep with detailed knowledge of hieroglyphs and the iconography of power, to reveal Ancient Egypt in all its complexity--from the brutality and repression that lay behind the appearance of its unchanging monarchy to its extraordinary architectural and cultural achievements.
Divine right (5000-2175 B.C.). In the beginning ; God incarnate ; Absolute power ; Heaven on Earth ; Eternity assured -- End of innocence (2175-1541 B.C.). Civil war ; Paradise postponed ; The face of tyranny ; Bitter harvest -- The power and the glory (1541-1322 B.C.). Order reimposed ; Pushing the boundaries ; King and country ; Golden Age ; Royal revolution -- Military might (1322-1069 B.C.). Martial law ; War and peace ; Triumph and tragedy ; Double-edged sword -- Change and decay (1069-30 B.C.). A house divided ; A tarnished throne ; Fortune's fickle wheel ; Invasion and introspection ; The long goodbye ; Finis.
"Originally published in the United Kingdom by Bloomsbury Publishing, Plc., London, in 2010"--T.p. verso.
Includes bibliographical references (p. [539]-578) and index.
Keywords: Egypt -- History -- To 332 B.C.; Egypt -- History -- 332-30 B.C.